The Emergence of the Horseman Sculpture in Tehran’s Urban Arts - Naseri, Elham; Nadalian, Ahmad (Journal of History Culture and Art Research, 2019)
The study tries to consider the procedure of construction and legitimization of a new kind of art and aesthetic. In Islamic period, we cannot trace the construction of three-dimensional (in European way) sculpture in Iran. It was in the Qajar era that Qoorkhaneh minister ordered some artists to sculpt Naser al-Din Shah’s sculpture (horseman). This model was followed in the next epochs such as Pahlavi and Islamic Republic. The research revolves around the question of how the horseman sculpture, in contrast to the previous aesthetic, emerged as a new aesthetic; and how it was accepted as a new kind of art. The article is purposely a fundamental-theoretical study and it is a descriptive-analytical study in term of nature. Methodologically, it is a qualitative study in which the researcher applies Foucauldian concept of power/knowledge to answer the above questions. Additionally, it tries to consider how a work becomes a branch of urban arts in Iran. The study comes to the conclusion that the effect of knowledge which exerted by power in the Qajar era as well as establishment of the institutions and diplomacies in national level produced a kind of discipline and training aesthetic sense. This training gradually persuades some artists to accept the aesthetic and sculpture style and consequently they design and perform some works based on this pattern.